Expanding Access to Computed Tomographic Staging and Three-Dimensional Intensity Modulated Radiotherapy for Cervical Cancer in Ghana - Aba Anoa Scott; Verna Vanderpuye; Mary-Ann Dadzie; Joel Yarney; Charles Akoto Aidoo; Judith Tackie; Stephen Kpatsi; Samuel Boateng; Tony Obeng-Mensah; Michael Nyamadi; Philip Odonkor; Tony Lam; et al. (JCO Global Oncology, 2024)
PURPOSETo build capacity for improved treatment of locally advanced cervical cancer in Ghana, including computed tomography (CT) staging and intensity modulated radiotherapy (IMRT).MATERIALS AND METHODSPatients with histologically confirmed cervical cancer were prospectively staged with abdominopelvic CT and ultrasound and offered the opportunity to have IMRT instead of conventional two-dimensional radiotherapy. The development of an efficient, high-quality, and safe IMRT program was facilitated by investment in new technology and comprehensive training of the interdisciplinary radiotherapy team in collaboration with a North American center of excellence.RESULTSOf 215 patients with cervical cancer referred in 2022, 66% were able to afford CT scans and 26% were able to afford IMRT. Lymph node metastases were identified in 52% of patients by CT but in only 2% of patients by ultrasound. The use of CT resulted in 63% of patients being upstaged and changed treatment intent or radiation treatment volumes in 67% of patients. Patients who had IMRT experienced fewer acute side effects and were more likely to complete treatment as planned.CONCLUSIONIt is feasible to provide state-of the-art cancer treatment with CT staging and IMRT to patients with cervical cancer in low-resource settings and achieve meaningful improvements in outcomes. It requires a broad commitment by program leadership to invest in technology and staff training. Major challenges include balancing improved clinical care with reduced patient throughput when radiation treatment capacity is constrained, and with the additional cost in the absence of universal health coverage.